PENGARUH REAKSI PASAR MODAL TERHADAP PERISTIWA AKSI DAMAI 4 NOVEMBER 2016 (Event Studi pada Saham Kompas 100 Yang Terdaftar Di Bursa Efek Indonesia) - Mulya, Lega Tri; Ritonga, Kirmizi (Jurnal Tepak Manajemen Bisnis, 2017)
This research aims to know and analyze the difference between abnormalreturn and trading volume activity before and after Peace Action in November 4, 2016.The Peace Action might give an effect on capital market. If the event runs peacefully, itwould have a positive impact to capital market. Otherwise, it would have a negativeimpact on the capital market. The population in this study was all companies listed inKompas100 Index. The method used was a comparison study by using Paired Sample TTest. Based on the results of data analysis and discussion, it can be concluded asfollows that The was no different between abnormal return and trading volumeactivity before and after the peace action in November 4, 20016. The implications ofthis research is If there are actions that are not an anarchist then the investors do nothave to worry to invest.